PENYULUHAN PARTISIPASI MASYARAKAT DALAM PENGEMBANGAN DESA WISATA - Taofik, Muhammad; Siti Humairoh, Rifa; Pratiwi, Galuh; Salsabila, Nalasyahla; Dwi Irfani, Tabina; Adi Laksono, Bayu (CV Bayfa Cendekia Indonesia Bekerjasama dengan Jurusan/Program Studi Pendidikan Masyarakat FKIP Universitas Siliwangi, 2023)
Village tourism is a part of tourism development that certainly requires community participation. One of the tourism villages that can be developed in Tasikmalaya Regency is Sukaasih Tourism Village. The Sukaasih Village Government and the community must participate and work together, in order to maximize all existing potential for sustainable tourism village development. The method used was counseling because based on a survey in the field, low community participation is one of the obstacles in the development of Sukaasih Tourism Village. The existence of community participation counseling activities in the development of this tourism village has a positive impact on the community because it can increase their knowledge and understanding of the benefits obtained by developing the village's potential to become a tourist attraction. With this awareness, Sukaasih Tourism Village can become a superior and quality tourism village so that the economic welfare of the community can increase according to the expected goals.